História das diversões em Rio Branco, 1918 – 1927 - Joyce Nancy da Silva Corrêa (2019)
The city of Rio Branco was marked by political conflicts, economic crisis and several administrative reorganizations throughout the first decades of the twentieth century. In this interim arises and develops different modalities of fun. Among them, plays, religious festivals, carnival, civic and private. Sports such as shooting, regatta and cross-country included the city's sport scene, but football was the most famous sport, with the creation of clubs, a league and tournament competition. Cinema, as well as football, was a well-known and enduring diversion, highlighting the Eden-Cinema, an important space in the history of Rio Branco to this day, for its historical value. These amusements had in common the involvement of people who made up the local elite. But there were "non-useful" amusements, which encompassed practices similar to those said useful, but were performed by people without social prestige. The diversions in Rio Branco arose in a period of economic crisis and had important factors to develop. These include market diversification, individual actions and human capital.